Social and Health System Complexities Impacting on Decision-Making for Utilization of Oncology and Palliative Care in an African Context: A Qualitative Study. Issue 3 (July 2020) - Agom, David A.; Allen, Stuart; Neill, Sarah; Sixsmith, Judith; Poole, Helen; Onyeka, Tonia C.; Ominyi, Jude
Background: There is a dearth of research focusing on identifying the social complexities impacting on oncology and palliative care (PC), and no study has explored how the health-care system in Nigeria or other African contexts may be influencing utilization of these services. Aim: This study explored how social complexities and the organization of health-care influenced the decision-making process for the utilization of oncology and PC in a Nigerian hospital. Methods: This qualitative study used an interpretive descriptive design. Data were collected using semistructured interview guides with 40 participants, comprising health-care professionals, patients, and their families. Thematic analysis was conducted to generate and analyze patterns within the data. Findings: Three themes were identified: dysfunctional structural organization of the health-care delivery system, service-users' economic status, and the influence of social networks. The interrelationship between the themes result in patients and their family members decisions either to present late to the hospital, miss their clinical appointments, or not to seek oncological health care and PC. Conclusion: This article offers insights into the role of the health-care system, as organized currently in Nigeria, as "autoinhibitory" and not adequately prepared to address the increasing burden of cancer. We therefore argue that there is a need to restructure the Nigerian health-care system to better meet the needs of patients with cancer and their families as failure to do so will strengthen the existing inequalities, discourage usage, and increase mortality.